Hemodynamic ischemia of the anterior choroidal artery and reversal by carotid artery stenting 10 years after ipsilateral superficial temporal artery-middle cerebral artery bypass for symptomatic left middle cerebral artery stenosis - Hayato Suzuki; Suguru Yamaguchi; Katsuhiro Nishino; Taizen Nakase; Hiroaki Shimizu (MDPI AG, 2018)
The pathogenesis of anterior choroidal artery (AChA) territory infarction includes various mechanisms, but hemodynamic causes are rare and difficult to diagnose. 77-year-old man, who had moderate left ICA stenosis and he had treated with STA-MCA bypass surgery for severe symptomatic left MCA stenosis 10 years earlier, was admitted with right hemiparesis and confused state. On admission, magnetic resonance imaging and angiography demonstrated patent bypass, but severe stenosis of left ICA with no opacification of the left AChA and A1 portion of the left ACA. Diffusionweighted imaging demonstrated ischemic lesion in the left corona radiata. Together with clinical findings, hemodynamic ischemia of the AChA region was suspected and left carotid artery stenting resulted in prompt improvement of symptoms. Hemodynamic ischemia of the AChA territory is rare, however, should be considered as a potential target of treatment when the ipsilateral ICA, A1 and M1 show stenoocclusive lesions.